Theme Park Fandom : Spatial Transmedia, Materiality and Participatory Cultures - Williams, Rebecca (Transmedia (Amsterdam, Netherlands), 2020)
This book argues that serious study of theme parks and their adult fans has much to tell us about contemporary transmediality and convergence, themed and immersive spaces, and audience relationships with places of meaning. Considering the duopoly of Disney and Universal in Orlando, the book explores a range of theme park experiences including planning trips, meeting characters, eating and drinking, engaging in practices such as cosplay and re-enactment, and memorializing lost attractions. Highlighting key themes such as immersion, materiality, cultural distinctions, and self-identity, the book argues that theme parks are a crucial site for the exploration of transmediality and the development of paratexts. Proposing the key concepts of spatial transmedia and haptic fandom, the book offers analysis of the intersections between fandom, media texts, and merchandise, as well as fans' own affective and physical responses to visiting the parks.